Obtaining and characterizing a biodegradable polymer from cassava starch (2006)
In this investigation a biodegradable polymer is obtained from cassava starch by processing mixtures of modified starch with glycerin and water as plasticizers, using an open mill and a single screw extruder. The variables to be controlled during extrusion are: temperature profile, torque, and spindle rotation speed. Mechanical and physicochemical characteristics are evaluated by stress tests, thermal analysis of Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA), Fourier Transformed Infrared Analysis (FTIR) and morphology.